Sustainable biowaste treatment with open-air & in-vessel composting - Keng, Zi Xiang (2024)
Biowaste remains a key challenge for solid waste management globally, typically related to the difficulty in source segregation, putrescible nature, diminishing value in short time and significant mass loss during conversion. This research was undertaken to assess the treatment of soybean curd residue (SCR), as a common food & beverage industrial biowaste, with two types of composting methods i.e. open-air and in-vessel. The feasibility of a communal-scale food waste composting project was reviewed in the third chapter. The project was developed in the campus of University of Nottingham Malaysia in Semenyih, Selangor since year 2016. In the following chapters, the research entails the industrial composting of SCR, which is the main research topic as this research collaboration project between University of Nottingham and KPT Recycle Sdn Bhd. The research methodology included the physical-chemical analysis of the open-air and in-vessel composting, the microbiological assessment and compost application with plot test. From the research analysis, it was found that the compost produced from the open-air composting (static pile, deposited method) in KPT Recycle Sdn Bhd exhibits several characteristics that are not in the common standard of a healthy compost, i.e. the moisture content of about 60%, organic matter of over 85% and pH of about 4-5. The primary amendment (bulking agent) for this SCR composting is sawdust. Compost maturity assessment (germination test and Solvita test) show that the compost is not matured. In comparison, the compost produced from a large-scale in-vessel composter fulfils the standard range of a good compost, i.e. moisture 30%, 50-60% organic matter and pH of 6-7. The average NPK of in-vessel compost (2:2:3) is also higher than NPK of open-air compost (2:1:2). During the activation of the in-vessel composter, it was found that the low pH and high moisture of SCR thwarted the achievement of thermophilic composting process. With optimum adjustment of pH and moisture, thermophilic process was attained. The robust analysis of compost maturity with Solvita test revealed that the compost maturity level for open-air compost is directly proportionate with the duration of composting i.e. the longer the period the higher the maturity level. While for in-vessel compost, direct discharge is not mature, but after one month of curing the compost discharge achieve a matured level (Solvita index 6). For microbial assessment, the common bacteria for open-air compost are Corynebacterium, Acetobacter and Bacillus smithii; while for in-vessel compost are Lactobacillus, Acetobacteraceae and Corynebacterium. The common fungi for open-air compost are Aspergillus, Thermomyces dupontii and Thermoascus crustaceus; while for in-vessel compost are Trichosporon, Sterigmatomyces and Pichia deserticola. IVC compost demonstrates a better effect in compost application, for one macronutrient (K) and anthocyanin, while OAC compost performs better for one micronutrient (Fe); while there were no differences between all the other parameters. The result indicates that effect of compost production methods on plant growth parameters (leaf area, root weight, chlorophyll, etc), macro and micronutrients uptake is not significant. In term of compost ratio, compost to soil in 1:3 ratio has the best effect for nutrient uptakes especially for P, Zn, and Cu. Based on the overall analysis, the compost prepared by IVC is better than OAC for both crops in terms of plant health and compost effectiveness.